"Asr Alhulm Wa'iikhfaq Alwaqie" "Captivating the Dream and the Failure of Reality" In the Poem of Ubaid Allah Bin Qais Al-Ruqayyat "'Alaa Huziyat Bina Qirashiatun" - Hussein Al-Zuhairi, Mahmoud (Dirasat: Human and Social Sciences, 2024)
Objectives: This aims to highlight the role of poetry in the game of politics, clarify the role of the intelligent poet in employing dream and imagination, using linguistic formulas and deep suggestive vocabulary that will lead him to his goal without questioning, and highlight the role of poetic expectations in arranging the details of the poem. Methods: This study relied on the descriptive analytical method because of its ability to analyze the suggestive linguistic dimensions within the text. Results: Sarcasm and mockery have a role and input into political criticism and opposition., being a painful spite for the opponent that achieves the goal in the shortest way. Hiding behind dreams is a way out that alleviates the severity of the situation. Exceptional poets can transform dreams into reality and reality into fantasy with astounding artistry, utilizing the richness of language and its connotations. Rhyme and its implications serve as key elements in the poetic text, symbolizing the poet's objectives. Conclusion: Ubaidullah bin Qais Al-Ruqayat, an experienced poet, employed satire to expose the Umayyads' dishonor, represented by Umm al-Banin, addressing the injustices his family faced in Al-Harrah. His use of rhythm and suggestive language aimed to ridicule and influence the audience, drawing on the rich artistic imagery of the Bedouin environment and praising Musab Ibn Al-Zubair to achieve his poetic goals effectively.